STUDI EKSPLORASI DAN KARAKTERISASI ANGGREK ALAM SECARA MORFOLOGI DALAM RANGKA PELESTARIAN PLASMA NUTFAH - SRI HARTATI; AGUS BUDIYONO; Ongko Cahyono (Fakultas Pertanian, Universitas Tunas Pembangunan Surakarta, 2014)
Morphological characters orchid species (natural) is very important to learn in order to support successful breeding orchids. Orchids of this species plays an important role as a parent crosses. The purpose of this study was to determine the morphological characteristics of orchid species and genetic diversity of natural orchids in Indonesia.Pelaksanaan some research done in the Faculty of Agriculture exsitu UTP Surakarta from May 2012 until November 2012 Rangcangan design used was Randomized Complete Block with three replications. Accession number consists of 12 orchid species, accession assumed as treatments and replications assumed as a group. Morphological characterization using a scoring guide Characterization of Ornamental Plants by Orchid. Cluster analysis performed by the program NTSYSpc version 2.02i with UPGMA method SimQual function. Dendrogram based on the similarity of 39% obtained by the two groups, the first group consists of Dendrobium liniale, Calanthe triplicate, crumenatum Dendrobium, Eria javanica, spathoglotis plicata, and Acriopsis javanica. The second group consisted of Cymbidium bicolor, Rhynchontylis retusa blume, Vanda tricolor var Suavis, Vanda tricolor var tri color and Vanda Limbata.